How is image seeking and use studied: Theoretical models and research methods: Sponsored by: SIG VIS, SIG AH, SIG DL, and SIG USE. Issue 1 (27th December 2016) - Matusiak, Krystyna K.; Rorissa, Abebe; Albertson, Dan; Yoon, JungWon
ABSTRACT: The digital revolution is associated with the proliferation of visual resources and with the increasing use of images in teaching, scholarly activities, communication, and everyday information practices. Visual information seeking and use is a growing area of research in information science. The panel discussion will focus on theoretical and methodological approaches to studying how users seek, select, apply, and organize visual information in a range of information and communication practices. The discussion about theory and research methodologies will be complemented by an example of an empirical study and an inquiry into implications of social media for image use research. The panel will contribute to a better understanding of the current state of image research and will engage the scholarly community in a debate about research methodology and theory development.